High-Frequency Variability of Bacterioplankton in Response to Environmental Drivers in Red Sea Coastal Waters - Ansari, Mohd Ikram; Calleja, Maria LI.; Silva, Luis; Viegas, Miguel; Ngugi, David Kamanda; Huete-Stauffer, Tamara Megan; Morán, Xosé Anxelu G. (Frontiers in Microbiology, 2022)
Autotrophic and heterotrophic bacterioplankton are essential to the biogeochemistry of tropical ecosystems. However, the processes that govern their dynamics are not well known. We provide here a high-frequency assessment of bacterial community dynamics and concurrent environmental factors in Red Sea coastal waters. Weekly sampling of surface samples during a full annual cycle at an enclosed station revealed high variability in ecological conditions, which reflected in changes of major bacterioplankton communities. Temperature varied between 23 and 34°C during the sampling period. Autotrophic (Synechococcus, 1.7–16.2 × 104 cells mL−1) and heterotrophic bacteria (1.6–4.3 × 105 cells mL−1) showed two maxima in abundance in spring and summer, while minima were found in winter and autumn. Heterotrophic cells with high nucleic acid content (HNA) peaked in July, but their contribution to the total cell counts (35–60%) did not show a clear seasonal pattern. Actively respiring cells (CTC+) contributed between 4 and 51% of the total number of heterotrophic bacteria, while live cells (with intact membrane) consistently accounted for over 90%. Sequenced 16S rRNA amplicons revealed a predominance of Proteobacteria in summer and autumn (>40%) and a smaller contribution in winter (21–24%), with members of the Alphaproteobacteria class dominating throughout the year. The contribution of the Flavobacteriaceae family was highest in winter (21%), while the Rhodobacteraceae contribution was lowest (6%). Temperature, chlorophyll-a, and dissolved organic carbon concentration were the environmental variables with the greatest effects on bacterial abundance and diversity patterns.